(MULTI-) FREQUENCY VARIATIONS OF STARS. SOME METHODS AND RESULTS - Andronov, I. L. (Одеські астрономічні публікації, 2017)
Some algorithms and programs are described for determining the parameters of processes with constant and variable periods. Those are: FOUR-1 periodogram analysis by using the least squares one-harmonic fit, FOUR-N corresponds to a number of harmonics, FOUR-T to a sine wave with a linear trend, FOUR-M to a number of waves with independent frequencies. Multishif-ted and mean weighted periodograms are discussed. PERMIN allows the determination of a best fit period from the moments of "characteristic events" only. The programs allows one to determine not only the parameters, but accuracy estimates and the " false alarm" probability as well. Some applications of these and some other methods to variable stars of different types are discussed.